Modelling and optimising the nexus between operating parameters of combine harvester and grain loss during harvest in Malaysian paddy field / Nor Azi Asminda Johari - Johari, Nor Azi Asminda (2022)
Paddy cultivation is one of the largest contributors to feeding Malaysian since it serves as a staple food. Harvesting is the most critical factor that should be given big attention in paddy cultivation since it directly affects the grain loss in the field. During the operation, improper management of some operating parameters, such as combine harvester handling and crop physiological factors, may lead to excessive grain loss. Five operating parameters usually affect the grain loss (GL), namely field speed (FS), grain moisture content (GMC), soil moisture content (SMC), soil compaction (SC), and cutting height (CH). However, the relationship between grain loss and these operating parameters of mechanized rice harvesting in Malaysia is rarely studied. Thus, the study was conducted to investigate the effect of these operating parameters on grain loss during the mechanized rice harvesting operation. Modelling and optimizing the significant operating parameters for predicting grain loss were also developed. Besides that, the simulation of the control system using MATLAB was designed based on the developed predictive empirical model for minimizing grain loss and evaluating the field performance of the rice combine harvester during harvesting operations. Lastly, the spatial variability maps towards the significant operating parameters and grain loss were also visualized. To collect the data, daily paddy harvesting operations with New Holland Clayson 8080 combine harvester were observed at rice granaries in the Sekinchan district of Selangor state of Malaysia through a field observation measurement method on December 2017. The total grain loss was measured based on the header loss test and processing loss test. Results from statistical analysis proved that operating parameters have highly significant effects on grain loss.